Andrew Porter, Religion versus Empire? British Protestant Missionaries and Overseas Expansion, 1700-1914: Policy and Politics of British Mission Organisations (Historia, 2021)
This is an ambitious book. Andrew Porter's sweeping history of British Protestant missions between 1700 and 1914 weaves together the vast scholarship and known history of mission policy while weighing in on the debate about the relationship between missions and empire. Those familiar with Porter's work will not find a new interpretation of mission history in this volume. However, because of the broad scope of information addressed, and ..